The mystery of the monarchs : how kids, teachers, and butterfly fans helped Fred and Norah Urquhart track the great monarch migration - Rosenstock, Barb (Alfred A. Knopf, 2022)
"Young Fred Urquhart was fascinated by insects, especially his favorite, the monarch butterfly. He wondered where monarchs spent the winter. No one knew. After he became an entomologist (bug scientist),Fred and his wife, Norah,tagged hundreds of butterflies,hoping to solve the mystery of the monarchs. But they soon discovered that they needed help. They started a "butterfly family," a community of children, teachers, and nature enthusiasts from three countries--Canada, the United States,and Mexico--to answer the question: Where do the monarchs go?" -- Amazon.com.